Effects of Seagrass Wasting Disease on Eelgrass Growth and Belowground Sugar in Natural Meadows - Graham, Olivia J.; Aoki, Lillian R.; Stephens, Tiffany; Stokes, Joshua; Dayal, Sukanya; Rappazzo, Brendan; Gomes, Carla P.; Harvell, C. Drew (Frontiers in Marine Science, 2021)
Seagrass meadows provide valuable ecosystem benefits but are at risk from disease. Eelgrass (Zostera marina) is a temperate species threatened by seagrass wasting disease (SWD), caused by the protist Labyrinthula zosterae. The pathogen is sensitive to warming ocean temperatures, prompting a need for greater understanding of the impacts on host health under climate change. Previous work demonstrates pathogen cultures grow faster under warmer laboratory conditions and documents positive correlations between warmer ocean temperatures and disease levels in nature. However, the consequences of disease outbreaks on eelgrass growth remain poorly understood. Here, we examined the effect of disease on eelgrass productivity in the field. We coupled in situ shoot marking with high-resolution imagery of eelgrass blades and used an artificial intelligence application to determine disease prevalence and severity from digital images. Comparisons of eelgrass growth and disease metrics showed that SWD impaired eelgrass growth and accumulation of non-structural carbon in the field. Blades with more severe disease had reduced growth rates, indicating that disease severity can limit plant growth. Disease severity and rhizome sugar content were also inversely related, suggesting that disease reduced belowground carbon accumulation. Finally, repeated measurements of diseased blades indicated that lesions can grow faster than healthy tissue in situ. This is the first study to demonstrate the negative impact of wasting disease on eelgrass health in a natural meadow. These results emphasize the importance of considering disease alongside other stressors to better predict the health and functioning of seagrass meadows in the Anthropocene.